Contrasting Key Bacteria and Fungi Related to Sugar Beet (Beta vulgaris L.) with Different Resistances to Beet Rot under Two Farming Modes - Ming Lin; Yuanhang Zhou; Runlai Xu; Chenghang Du; Ronghua Wang; Weidan Lu; Kuerban Abudukadier; Zhencai Sun (Agronomy, 2023)
Sugar beet production is threatened by beetroot rot, which can be triggered by consecutive monoculture. Previous studies have shown the beneficial function of microbes affiliated with different plant compartments in inhibiting various plant pathogens. However, whether sugar beet root can recruit particular microbes at the risk of beet rot is still unclear. Therefore, this study explored the composition and community structure of bacteria and fungi of the different compartments (endosphere root, rhizosphere, bulk soil) under two farming modes (monoculture and rotation). Our result showed that the farming mode significantly affected the community structure of bacteria and fungi in bulk soil. In the rhizosphere, the community structures of bacteria between the two varieties were similar under rotation mode, and markedly different under monoculture mode. The bacterial and fungal diversity in the rhizosphere and endophytic root of the rot-suppressive variety was higher than in the rot-conducive variety. Under monoculture mode, the beneficial microbes as biomarkers were enriched in the rot-resistant variety, e.g., operational taxonomic units (OTUs) affiliated to the genus of Sordariomycetes, Cordycipitaceae, Lecanicillium, Plectosphaerellaceae, S085, Pedosphaeraceae in the rhizosphere and the genus of Actinobacteria, and Pseudonocardia, Exobasidiomycetes in the endophytic root, while for the rot-conducive variety, OTUs affiliated to the genus of Chitinophagaceae, Flavisolibacter in the rhizosphere and the Novosphingobium, Sphingobacterium, Tilletiopsis_washingtonensis, and Flavobacterium in the endophytic root. The network analysis showed that OTUs affiliated to the order of Saccharimonadales, Anaerolineae, the family of Saprospiraceae, the genus of Subgroup_10 (belonging to the family of Thermoanaerobaculaceae), Lysobacter, and AKYG587 were the keystone taxa in the rot-suppressive variety, while both beneficial and harmful microbes in the rot-conducive variety, such as Pedobacter, Ferruginibacter, and P3OB-42, were present. The variation in soil pH was shown to be the critical contributor to the microbial difference. In summary, the farming mode is critical in shaping bulk soil microbial structure by changing soil pH. Under monoculture mode, the rot-suppressive variety has more microbial diversity in both the rhizosphere and endophytic root, and enriched different beneficial microbes relative to the rot-conducive variety; the underlying mechanisms and associations of critical microbes are worth further investigation.